2022
DOI: 10.4103/amit.amit_64_22
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Analyze the Effect of Gabapentin with Amitriptyline Versus Pregabalin with Amitriptyline in Neuropathic Pain in Cancer Patients Undergoing Palliative Care

Abstract: Introduction: Antiepileptics and antidepressant medications are known for managing neuropathic pain. We aim to compare the effects of pregabalin with low-dose amitriptyline and gabapentin with low-dose amitriptyline in managing neuropathic pain in cancer patients undergoing palliative care. Materials and Methods: We conducted our study on 160 cancer patients who were having neuropathic pain and were undergoing palliative care treatment in our institute.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…13 Similar to our study Lamba et al found that in the management of neuropathic pain in cancer patients who are undergoing palliative care, a combination of pregabalin with amitriptyline was found to be more effective in pain relief than gabapentin with amitriptyline. 14 In present study we found that gabapentin had more side effects than pregabalin in terms of more episodes of drowsiness, headache, blurring of vision with the use of gabapentin, whereas with pregabalin few patients suffered from sedation and nausea. Similar to our study, Madhanagopal et al stated that pain relief was better in the pregabalin group than in gabapentin and placebo with an equal incidence of adverse effects except for nausea which was more in the pregabalin group.…”
Section: Discussionsupporting
confidence: 43%
“…13 Similar to our study Lamba et al found that in the management of neuropathic pain in cancer patients who are undergoing palliative care, a combination of pregabalin with amitriptyline was found to be more effective in pain relief than gabapentin with amitriptyline. 14 In present study we found that gabapentin had more side effects than pregabalin in terms of more episodes of drowsiness, headache, blurring of vision with the use of gabapentin, whereas with pregabalin few patients suffered from sedation and nausea. Similar to our study, Madhanagopal et al stated that pain relief was better in the pregabalin group than in gabapentin and placebo with an equal incidence of adverse effects except for nausea which was more in the pregabalin group.…”
Section: Discussionsupporting
confidence: 43%